Vacuum arc ion and plasma source Raduga-5. Technological applications; Korus 2001; Vol. 1 - Ryabchikov A. I. Aleksandr Ilyich; Stepanov I. B. Igor Borisovich; Dektyarev S. V. Sergey Valentinovich; Shulepov I. A. Ivan Anisimovich; Lukonin E. I. Evgeny Ivanovich; Sivin D. O. Denis Olegovich (2001, 2001)
The paper discusses examples of realizing the regimes of high-intensity and high-concentration ion implantation, and plasma deposition of coatings including the conditions of dynamic ion mixing using "Raduga-5", a source of accelerated ions and plasma based on the DC vacuum arc discharge. It is shown that when a target is treated with high average power beams, it is possible to dope a material at depths exceeding the projective ion range by an order of magnitude. Features of ion beam application at different stages of ion plasma deposition of coatings are considered. Examples are given for the formation of wide transition layers between the coating and the substrate under conditions of intensive ion mixing. Mechanisms of change in the properties of the coatings formed with decreasing microparticle fractions in the arc plasma stream are considered